Agriculture and climate change: Agricultural science and technology needs for climate change adaptation and mitigation - Rabbinge, R. (International Food Policy Research Institute, 2009)
Higher temperatures, more variable precipitation, and changes in the frequency and severity of extreme climate events will have significant consequences for food production and food security. However, the frequency of heat stress, drought, and flooding are also expected to increase, even though they cannot be modeled satisfactorily with current climate models. They will undoubtedly have adverse effects on crops and agricultural productivity over and above the effects due to changes in mean variables alone. The impacts of climate change on agriculture are likely to be regionally distinct and highly heterogeneous spatially, requiring sophisticated understanding of causes and effects and careful design and dissemination of appropriate responses. These changes will challenge the livelihoods of farmers, fishers, and forest-dependent people who are already vulnerable and food insecure. Adapting to these changes, while continuing to feed a world of 9 billion people, requires the formation of a global partnership in science, technology development, and dissemination of results to millions of smallholder farmers, bringing together research workers and resource managers from many fields. To take an international approach to climate change, new partnerships must be forged, linking the agricultural research and climate science communities.